Gold-potassium sheets intercalated into graphite: Chemistry and structure of a first stage ternary compound. (December 2018) - Fauchard, Mélissa; Cahen, Sébastien; Lagrange, Philippe; Medjahdi, Ghouti; Berger, Pascal; Hérold, Claire
Abstract: A ternary graphite-potassium-gold compound K1.3 Au1.5 C4 was synthesized by immersing a pyrographite platelet in various potassium metal-based molten alloys. Numerous reaction parameters were investigated (duration, temperature, composition of the alloy) in order to determine the stability conditions of the ternary compound. Using complementary X-ray diffraction and ion beam analysis experiments, the optimal conditions of preparation of this compound have been pointed out. The composition and homogeneity were evidenced by ion beam analysis and X-ray diffraction allowed to determine its repeat distance (1311 pm) and its c-axis stacking sequence (K-Au-Au-Au-K). The 2D unit cell observed thanks to Transmission Electron Microscopy (TEM) is square with a = 1192 pm, no-commensurate with that of graphite. Graphical abstract: Image